Dependence Potential of the Synthetic Cannabinoids JWH-073, JWH-081, and JWH-210: In Vivo and In Vitro Approaches - Cha, Hye Jin (The Korean Society of Applied Pharmacology, 2014)
Synthetic cannabinoids (CBs) such as the JWH series have caused social problems concerning their abuse liability. Because the JWH series produces euphoric and hallucinogenic effects, they have been distributed illegally under street names such as “Spice” and “Smoke”. Many countries including Korea have started to schedule some of the JWH series compounds as controlled substances, but there are a number of JWH series chemicals that remain uncontrolled by law. In this study, three synthetic CBs with different binding affinities to the CB(1) receptor (JWH-073, 081, and 210) and Δ(9)-tetrahydrocannabinol (Δ(9)-THC) were evaluated for their potential for psychological dependence. The conditioned place preference test (unbiased method) and self-administration test (fixed ratio of 1) using rodents were conducted. K(i) values of the three synthetic cannabinoids were calculated as supplementary data using a receptor binding assay and overexpressed CB(1) protein membranes to compare dependence potential with CB(1) receptor binding affinity. All mice administered JWH-073, 081, or 210 showed significantly increased time spent at unpreferred space in a dose-dependence manner in the conditioned place preference test. In contrast, all tested substances except Δ(9)-THC showed aversion phenomenon at high doses in the conditioned place preference test. The order of affinity to the CB(1) receptor in the receptor binding assay was JWH-210 > JWH-081 >> JWH-073, which was in agreement with the results from the conditioned place preference test. However, no change in self-administration was observed. These findings suggest the possibility to predict dependence potential of synthetic CBs through a receptor binding assay at the screening level.